Synthesis, structure-activity relationship and solubility improvement studies of potential antimalarial and antischistosomal pyrido[1,2-a]benzimidazoles - Chisanga, Kelly (Department of Chemistry, 2020)
In 2016, 216 million malaria cases with 445,000 associated deaths were recorded according to the World Health Organization (WHO). Schistosomiasis also remains a public health issue with 207 million cases recorded globally and 280,000 deaths in the same year. Widespread emergence of parasite resistance to once-effective antimalarial options has rendered currently used drugs ineffective. Moreover, the current WHO-recommended first-line antimalarial drugs in clinical use, the artemisinin combination therapies (ACTs) are faced with the challenges of limited availability, unaffordable cost, and undesirable adverse effects. On the other hand, the treatment of schistosomiasis is severely limited to one treatment regimen, praziquantel (PQZ) which, unfortunately, has recently shown low curing rates in some parts of West Africa. Furthermore, this treatment option is far from ideal because its activity is limited to only adult schistosomes while displaying no activity towards young stages of the liver flukes. These challenges collectively provide a justification for stepping up drug discovery and development efforts aimed at identifying novel, safe and efficacious antimalarial and antischistosomal agents. Whereas, the pyrido[1,2-a]benzimidazole (PBI) scaffold is found in many pharmacologically relevant molecules including Rifaximin, an approved gastrointestinal antibacterial drug, medicinal chemistry explorations around the PBI nucleus have recently identified analogues as novel antimalarial and antischistosomal agents. Additionally, while promising antimalarial efficacy has been demonstrated in animal studies, preliminary in vitro studies of the PBI class of compounds have also demonstrated good activity against Schistosoma parasites. Recently, Mayoka reported the impressive dual antiparasitic potency of the lead compound GMP-19 (figure 1) against Plasmodium and Schistosoma parasites in vitro (IC50 = 0.430 μΜ, drug sensitive strain (NF54) and IC50 = 0.210 μΜ, adult S. mansoni, (unpublished data)). However, GMP-19 and other PBI analogues in this series of compounds, have been beset by poor solubility. Towards addressing solubility issues while retaining and improving antiparasitic activity, in this MSc dissertation, the design, synthesis, structure-activity relationship (SAR) and solubility improvement studies of PBI analogues based on the GMP-19 template are reported. In this regard, chemical modification approaches such as disruption of molecular planarity, increasing saturation, incorporating water solubilizing groups such as the polar-ionizable and the neutralpolar functionalities around the PBI nucleus were adopted. Consequently, we obtained SAR 1analogues after substituting the 4-(trifluoromethoxy)phenyl (4-OCF3Ph) moiety of GMP-19 with assorted α-methyl benzylamines. In addition, the phenyl ring on the left-hand side of the core scaffold was substituted with electron withdrawing groups such as the chloro and fluoro atoms (SAR 1.1 - 1.4), (figure 1). Although some analogues demonstrated a significant loss of antiparasitic activity (> 6.00 μM), strong submicromolar antiparasitic activity was observed with most analogues (IC50 = 0.022 -0.940 μM, PfNF54 and 30 - 69% inhibitory effect at 0.370 μM, against young forms of S. mansoni). Moreover, some analogues demonstrated poor solubility as low as < 10 μM while others showed highly improved solubility as good as 80 μM. In SAR 2.1 - 2.2, the 4-OCF3Ph and the trifluoromethyl (CF3) on the right-hand side (RHS) of the scaffold were fixed while introducing amino moieties (R) on the lipophilic phenyl ring on the left-hand side (LHS) of the PBI core (figure 2). Upon identifying the moiety with the best balance of solubility and biological activity, the 4-OCF3Ph was replaced with various acyclic amino (SAR 2.3) while the CF3 was maintained on C-3 of the core scaffold. Finally, the CF3 was replaced with the 4-CF3Ph (SAR 2.4 and 2.5) while keeping fixed the optimal basic amine and the acyclic amino moieties on the LHS, respectively. Interestingly, the pursued structural modifications delivered analogues with a wide diversity of pharmacological and physicochemical properties. While some analogues demonstrated significant loss of pharmacological activity, others exhibited potent submicromolar antiparasitic activity (IC50 < 0.012 - 0.990 μM, PfNF54 and 0.360 - 0.850 μM, adult S. mansoni). Similarly, some analogues demonstrated poor solubility as low as < 10 μM while others demonstrated improved solubility as good as 180 μM.